2021
DOI: 10.20448/journal.509.2021.81.103.108
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Gamified Learning Tool in the ESL Classroom: The Case of Quizizz

Abstract: Embracing gamification in education is, indeed, inevitable, especially with the arrival of the millennials whose lives are greatly influenced by digital technologies and favor learning in a fun, interactive, and engaging environment. Quizizz, a gamified educational tool, has gradually gained the interest of researchers and stakeholders in education as this application has presented positive outcomes towards learning with the integration of unique game elements such as leader boards, memes, and quiz reports, ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 12 publications
4
35
0
2
Order By: Relevance
“…Furthermore, in research conducted by Ahmad et al [16], it was discovered that teachers find Quizizz very effective because it is highly efficient at promoting students' enthusiasm to learn the language, even more so than other online learning platforms. This is supported by Yunus and Tan [21], who stated that teachers agree that Quizizz is effective because students achieve self-satisfaction while using the platform. In their study, they also learned that Quizizz is effective in the sense that it helps students to learn on their own through memory retention.…”
Section: Teachers' Perspective On the Effectiveness Of Quizizzmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, in research conducted by Ahmad et al [16], it was discovered that teachers find Quizizz very effective because it is highly efficient at promoting students' enthusiasm to learn the language, even more so than other online learning platforms. This is supported by Yunus and Tan [21], who stated that teachers agree that Quizizz is effective because students achieve self-satisfaction while using the platform. In their study, they also learned that Quizizz is effective in the sense that it helps students to learn on their own through memory retention.…”
Section: Teachers' Perspective On the Effectiveness Of Quizizzmentioning
confidence: 77%
“…Meanwhile, the results on teachers' willingness to use Quizizz in their classes could also be seen in the selected articles. Most teachers in the research conducted had a positive outlook on Quizizz and were willing to incorporate the platform in the future [14][15][16][17]19,[21][22][23][24][25]27,28,[30][31][32][33][34][35][36][37][38]40,41,[43][44][45][46]48,50,51,[53][54][55]57,58]. The findings on teachers' willingness to use Quizizz, which is related to this review's second research question, are shown in Table 5.…”
Section: Teachers' Willingness To Continue Using Quizizz In the Classroommentioning
confidence: 99%
“…Another research, Darmawan, Daeni, & Listiaji [11] uses Quizizz as an online assessment for science learning and concluded that online assessment using Quizizz is very beneficial for teachers or lecturers because they can provide test results reports quickly along with their analysis and increased student motivation and interest. Anak Yunus & Hua [12] in their research concluded that implementation of online interactive games such as Quizizz can be seen as an exhilarating, creative, and impactful means of shifting from the conventional way of imparting knowledge, especially to millennials. This educational game provides so many benefits that can certainly be felt in learning media, because this media is interesting and can motivate brain work and time management [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Quizizz, one of the formative assessment approaches that provide feedback on students’ performance, is a Web 2.0 tool that can be used by many people working on questions on an interactive and entertaining screen (Permana & Permatawati, 2020; Sheng et al., 2019). The use of Quizizz in education positively affects student participation and learning outcomes (Zhao, 2019), and is beneficial in language teaching, increases vocabulary (Anak Yunus & Hua, 2021), and can be used to measure analytical skills (Anggraeni & Taufiq, 2021).…”
Section: Introductionmentioning
confidence: 99%